Early Outcomes in Children With Antineutrophil Cytoplasmic Antibody–Associated Vasculitis. Issue 7 (9th June 2017) - Morishita, Kimberly A.; Moorthy, Lakshmi N.; Lubieniecka, Joanna M.; Twilt, Marinka; Yeung, Rae S. M.; Toth, Mary B.; Shenoi, Susan; Ristic, Goran; Nielsen, Susan M.; Luqmani, Raashid A.; Li, Suzanne C.; Lee, Tzielan; et al.
Abstract : Objective: To characterize the early disease course in childhood‐onset antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV) and the 12‐month outcomes in children with AAV. Methods: Eligible subjects were children entered into the Pediatric Vasculitis Initiative study who were diagnosed before their eighteenth birthday as having granulomatosis with polyangiitis (Wegener's), microscopic polyangiitis, eosinophilic granulomatosis with polyangiitis (Churg‐Strauss), or ANCA‐positive pauci‐immune glomerulonephritis. The primary outcome measure was achievement of disease remission (Pediatric Vasculitis Activity Score [PVAS] of 0) at 12 months with a corticosteroid dosage of <0.2 mg/kg/day. Secondary outcome measures included the rates of inactive disease (PVAS of 0, with any corticosteroid dosage) and rates of improvement at postinduction (4–6 months after diagnosis) and at 12 months, presence of damage at 12 months (measured by a modified Pediatric Vasculitis Damage Index [PVDI]; score 0 = no damage, score 1 = one damage item present), and relapse rates at 12 months. Results: In total, 105 children with AAV were included in the study. The median age at diagnosis was 13.8 years (interquartile range 10.9–15.8 years). Among the study cohort, 42% of patients achieved remission at 12 months, 49% had inactive disease at postinduction (4–6 months), and 61% had inactive disease at 12 months. The majority of patients improved, even if they did not achieve inactive disease. An improvement in the PVAS score of at least 50% from time of diagnosis to postinduction was seen in 92% of patients. Minor relapses occurred in 12 (24%) of 51 patients after inactive disease had been achieved postinduction. The median PVDI damage score at 12 months was 1 (range 0–6), and 63% of patients had ≥1 PVDI damage item scored as present at 12 months. Conclusion: This is the largest study to date to assess disease outcomes in pediatric AAV. Although the study showed that a significant proportion of patients did not achieve remission, the majority of patients responded to treatment. Unfortunately, more than one‐half of this patient cohort experienced damage to various organ systems early in their disease course.